(untitled) (Journal of Atomic and Molecular Sciences, 2017)
The potential energy curves (PECs) of NO (X²Π) have been studied employing a multi-reference configuration interaction method with the Davidson correction and with a series of Dunning's correlation-consistent basis sets: aug-c.c.-pvxz(x=T, Q, 5 and 6). Then computed PECs are extrapolated to the complete basis set limit. PECs are used to reduce the analytical potential energy functions (APEFs), accurate extended Hartree-Fork methods have been used to investigate electronic structure spectroscopy. Through the use of the extended Hartree-Fock approximate correlation energy method to fit APEF, we can calculate the spectroscopic parameters, consisting with the experimental and theoretical results, and we can also get the vibrational energy levels, classical turning points, centrifugal distortion constants and inertial rotation. Our calculations are sufficient to close into experimental data from other reference, so the results can supply a useful reference for future experiments.